Local trajectory parameters estimation and detection of moving targets in Rayleigh noise - Prokopenko, I.G.; Vovk, V.Iu.; Omelchuk, I.P.; Chirka, Yu.D.; Prokopenko, K.I. (Технология и конструирование в электронной аппаратуре, 2014)
The problem of detection of moving targets and estimation of local trajectory parameters based on the analysis of sensor data in the form of two-dimensional image is considered. In accordance with the target and sensor models, probability distribution of noise at the output of the detector is Rayleigh distribution, while probability distribution of signal is Rice distribution. Two trajectory parameters estimation techniques are considered: ordinary least squares and Hough transform. A detection stage based on the integration of an input signal along estimated trajectory is proposed. Statistical modeling was performed and detection characteristics were obtained.